Efektivitas Flukonazol dalam Mencegah Infeksi Jamur Invasif pada Bayi dengan Berat Lahir Sangat Rendah: Tinjauan Sistematis dan Meta-analisis - Fonny Cokro; Lorensia Yolanda; Shelly Caroline (Fakultas Farmasi Universitas Pancasila, 2022)
Fungal infections in neonates, especially in Very Low Birth Weight (VLBW) infants, are mostly caused by Candida species and may lead to morbidity and mortality. A systematic review and a meta-analysis were conducted to determine the extent to which fluconazole, an antifungal prophylactic, was effective and safe to use in VLBW or premature infants in preventing Invasive Fungal Infection (IFI), by including Randomized Controlled Trials (RCTs) carried out worldwide. The investigation started with searching process through publication databases: MEDLINE, Cochrane, ScienceDirect, and Garuda, for Randomized Controlled Trials (RCTs) that compared the prophylactic effects of fluconazole and placebo on IFI in VLBW infants. The selected eight RCT studies indicated that, compared to placebo, fluconazole accounted for 68% risk reduction of overall fungal colonization (RR=0.32; 95% confidence interval [CI]=0.24-0.42, p=0.00001, I-square=0%) and 60% risk reduction of IFI (RR=0.40; 95%[CI]=0.22-0.72, I-square=56%, p=0.002). However, fluconazole did not significantly reduce mortality in VLBW infants (RR=0.79; 95%[CI]=0.60-1.03; p=0.08, I-square=0%). Also, regarding its safety, fluconazole prophylaxis did not result in significant elevations of SGOT/SGPT levels (RR=1.22; 95%[CI]=0.50-3.00, p=0.66, I-square=0%) nor cause intestinal perforation (RR=0.96; 95%[CI]=0.25-3.68, p=0.96, I-square=59%). Fluconazole is an effective prophylaxis agent against invasive fungal infection when given to preterm infants with birth weight <1500, but not proven in reducing the mortality incidence in VLBW infants.